Targeting the Wnt signaling pathway in colorectal cancer. (2nd April 2016) - Sawa, Masaaki; Masuda, Mari; Yamada, Tesshi
Abstract : Introduction: The treatment of patients with advanced colorectal cancer still remains challenging, and identification of new target molecules and therapeutic avenues remains a priority. The great majority of colorectal cancers have mutations in one of two genes involved in the Wnt signaling pathway: the adenomatous polyposis coli ( APC ) and β-catenin ( CTNNB1 ) genes. Up to now, however, no therapeutics for targeting this pathway have been established. Areas covered: This review article begins with a brief summary of Wnt signaling from the viewpoints of genetics, cancer stem cell biology, and drug development. We then overview current attempts to develop drugs directed at various components of the Wnt signaling pathway. Expert opinion: APC is a tumor suppressor, and therefore only downstream signal transducers of the APC protein can be considered as targets for pharmaceutical intervention. TRAF2 and NCK-interacting protein kinase (TNIK) was identified as the most downstream regulator of Wnt signaling by two independent research groups, and several classes of small-molecule inhibitors targeting this protein kinase have been developed. TNIK is a multifunctional protein with actions that extend beyond Wnt signaling regulation. Such TNIK inhibitors are expected to have a large variety of clinical applications.